2010
DOI: 10.1016/j.molimm.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-factor B autoantibody in dense deposit disease

Abstract: Dense deposit disease (DDD), also known as membranoproliferative glomerulonephritis type II, is a rare kidney disorder that is associated with dysregulation of the alternative pathway of complement. Autoantibodies against the C3bBb convertase termed C3 nephritic factor are common in DDD patients. Here we report an autoantibody that binds to complement factor B in a DDD patient who was negative for C3 nephritic factor. This anti-factor B autoantibody recognized an epitope within the Bb fragment and was able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 39 publications
1
75
2
2
Order By: Relevance
“…The different phenotypes reflect antibody specificity for either the amino-or carboxy-terminal SCRs of FH, respectively. There has also been a single report describing a FBAA-positive DDD patient (44). In both that patient and the three FBAA-positive DDD patients in our study, the antibody also showed affinity for C3 convertase but not for other individual complement proteins.…”
Section: Discussionsupporting
confidence: 61%
“…The different phenotypes reflect antibody specificity for either the amino-or carboxy-terminal SCRs of FH, respectively. There has also been a single report describing a FBAA-positive DDD patient (44). In both that patient and the three FBAA-positive DDD patients in our study, the antibody also showed affinity for C3 convertase but not for other individual complement proteins.…”
Section: Discussionsupporting
confidence: 61%
“…Acquired dysregulation of the alternative pathway due to neutralizing autoantibodies against CFH [20] has also been described. Recently, an autoantibody to factor B, an activation protein within the alternative pathway, has also been associated with MPGN [21]. In summary factors that increase alternative pathway activation h a v e b e e n a s s o c i a t e d w i t h M P G N i n w h i c h there is glomerular C3 with little or no immunoglobulin.…”
Section: Complement and Mpgnmentioning
confidence: 99%
“…Autoantibodies may be directed against the complementregulating factors, such as factor H, factor I, factor B as well as against C3 convertase itself [55,56] . The first described autoantibody was the C3 ne phritic factor (C3 NeF), which binds and stabilizes C3 convertase [57] .…”
Section: Pathophysiologymentioning
confidence: 99%